China’s belt and road initiative progress towards Malaysia’s development: Where are we heading after the first decade? - Abd Rahman, Muhamad Azwan (Universiti Utara Malaysia Press, 2022)
Malaysia-China cooperation since normalization in 1974 has proceeded relatively well for the benefit of both countries. The prior role of Malaysia in offering the “hand of friendship” to China has reflected diplomatic co-existence in mutual trade, regional development and people-to-people relations. However, the close relationship between Malaysia and China has also impacted the position of Malaysia in joining China in the “One Belt One Road” (OBOR), which then changed to the Belt and Road Initiative (BRI). The agenda through the BRI, launched in 2013 under the leadership of Xi Jinping, has mapped out new promising relations in various dimensions (economic, financial, technical, etc.) with Malaysia and other countries in Southeast Asia through the 21st Century Maritime Silk Road or commonly known as the Maritime Silk Road (MSR). The BRI in Malaysia has created different patterns of mutual trust on the developmental scape although there has been little discussion since it was introduced. Therefore, this article intends to fill the gap by providing an analysis on its ongoing cooperation with China since Malaysia signed on to the BRI in 2013. This analysis is placed within the context of the Malaysia-China cooperation before and ongoing projects in BRI, the people-to-people and government-to-government relations in managing the COVID-19 pandemic and the geopolitics of China’s manoeuvres in the South China Sea. Much needs to be done to strengthen cooperation through the BRI between China and Malaysia particularly as 2023 marks the first decade of this mega project, given the emerging trust deficit in the ASEAN region with regard to China’s strategic goals in her competition with the US for power and influence.